2017
DOI: 10.1186/s40759-017-0020-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimal selection of operating parameters in end milling of Al-6061 work materials using multi-objective approach

Abstract: Background: Machining using vertical CNC end mill is popular in the modern material removal industries because of its ability to remove the material at a fast rate with a reasonably good surface quality. Methods: In this work, the influence of important common machining process variables like feed, cutting speed and axial depth of cut on the output parameters such as surface roughness and amplitude of tool vibration levels in Al-6061 workpieces has been studied. With the use of experimental result analysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…The surface plots of 3D model are provided with two factors at the same time. These fixed levels of the response factors provide the interaction information effects the two input factors, which helps to optimize level for each variable to obtain the maximum response [19].…”
Section:   mentioning
confidence: 99%
“…The surface plots of 3D model are provided with two factors at the same time. These fixed levels of the response factors provide the interaction information effects the two input factors, which helps to optimize level for each variable to obtain the maximum response [19].…”
Section:   mentioning
confidence: 99%
“…Individuals with best characteristics constitute the best solution to the problem; (5) this process continues in a repetitive manner until convergence criteria are met, i.e., the chromosomes have the best fitness or potential (optimum) solution for a specific problem is obtained. Immediately after the new generation is created, it is further assessed and checked through experimentation for the conformability and agreement (Shaik and Srinivas 2017).…”
Section: Optimization Using Genetic Algorithmmentioning
confidence: 99%
“…e authors used stir cast Alumina reinforced Aluminum Metal Matrix Composites (AAMMC) and found that the cutting speed (1750 rev/min), feed rate (0.3 mm/rev), and depth of cut (0.2 mm) are the optimum parameters for end milling operations. Shaik and Srinivas used the neural network-based RSM to find the optimum process parameter combination [10] for end milling operations in AA-6061 work material using a multiobjective approach. e authors found that the cutting speed of 1800.954 rpm, feed rate of 41.826 mm/min, and axial depth of 0.799 mm are the optimum combination for machining the AA-6061 material.…”
Section: Introductionmentioning
confidence: 99%